2022
DOI: 10.1177/10711007211069123
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Fifth Metatarsal Fractures: A Retrospective Study of 834 Fractures With a Minimum Follow-up of 5 Years

Abstract: Background: Proximal fifth metatarsal fractures are common fractures. Treatment strategies have been debated. We wanted to investigate whether Lawrence and Botte’s classification has prognostic value because of time to fracture union, and evaluate if weightbearing as tolerated (WBAT) and nonweightbearing (NWB) treatment strategy had effect on time to fracture union in nonoperatively treated fractures. Methods: Computerized database search, patients diagnosed between January 1, 2003, and December 31, 2015. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Early functional weight-bearing status and return to activity seem to have more of an impact and lead to excellent and quicker clinical outcomes. 5,7,20,22,23 A study by Vertullo et al 24 revealed that the ability of operative fixation to sufficiently resist torsional strain at the fracture site and create a stable load dispersion throughout the foot may be a reason why operative patients seem to have quicker clinical improvement, return to full weight-bearing, and return to sport. Factors that contribute to adverse outcomes include female sex, diabetes mellitus, and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Early functional weight-bearing status and return to activity seem to have more of an impact and lead to excellent and quicker clinical outcomes. 5,7,20,22,23 A study by Vertullo et al 24 revealed that the ability of operative fixation to sufficiently resist torsional strain at the fracture site and create a stable load dispersion throughout the foot may be a reason why operative patients seem to have quicker clinical improvement, return to full weight-bearing, and return to sport. Factors that contribute to adverse outcomes include female sex, diabetes mellitus, and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal fifth metatarsal fractures are among the most common foot fractures, with an incidence rate of 21 to 46 per 100,000 persons per year (0.021 to 0.046%) [16,50]. Incidence among football players, however, is significantly higher: 86 Jones fractures were identified in 83 athletes out of 4738 participants (incidence rate of 1.8%) in the NFL Combine, and 42 Jones fractures were identified during the 2010 to 2015 NFL seasons [34,47].…”
Section: Jones Fracturementioning
confidence: 99%
“…Pettersen et al [50] found that union rates for 834 nonoperatively treated proximal fifth metatarsal fractures were 97.3% for zone 1, 96.8% for zone 2, and 92.5% for zone 3. In addition, Josefsson reported a rate of union over 95% with satisfactory long-term functional outcomes by cast immobilization [24].…”
Section: Jones Fracturementioning
confidence: 99%
“…These authors from Grålum (Norway) have refocused us on the fifth metatarsal and the potential problems these patients can face. 7 Using the Lawrence and Botte classification, they set out to establish if the classification was capable of distinguishing between those patients who were likely to suffer either delayed or nonunion. Their cohort of 834 fractures was identified from a computer coding search.…”
Section: What Happens To the Base Of Fifth Metatarsal Fractures?mentioning
confidence: 99%